2009
DOI: 10.1111/j.1439-0310.2009.01618.x
|View full text |Cite
|
Sign up to set email alerts
|

Handling Stress as a Measurement of Personality in Great Tit Nestlings (Parus major)

Abstract: Interest in personality is growing in a wide range of disciplines, but only in a few systems it is possible to assess the survival value of personality. Field studies looking at the relationship between personality and survival value early in life are greatly hampered by the fact that personality can at present only be assessed after individuals become independent from their parents. In passerines, for example, this is often after a period of intensive selection for the survival on fledglings. The main aim of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
106
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(111 citation statements)
references
References 40 publications
(49 reference statements)
1
106
4
Order By: Relevance
“…after aggressive conflicts and cognitive challenge (Levins et al 2001;Maestripieri et al 1992) and the baseline anxiety (Aureli and de Waal 1997;Schino et al 1996). Some primate and bird studies have found covariation between anxiety and social behaviour (Papio anubis: Virgin and Sapolsky 1997; Pan troglodytes: Anestis 2006) and exploration tendency (Parus major: Fucikova et al 2009). In contrast, anxiety is encompassed by an independent construct, namely neuroticism, in the Five-Factor Model of human personality.…”
Section: Discussionmentioning
confidence: 99%
“…after aggressive conflicts and cognitive challenge (Levins et al 2001;Maestripieri et al 1992) and the baseline anxiety (Aureli and de Waal 1997;Schino et al 1996). Some primate and bird studies have found covariation between anxiety and social behaviour (Papio anubis: Virgin and Sapolsky 1997; Pan troglodytes: Anestis 2006) and exploration tendency (Parus major: Fucikova et al 2009). In contrast, anxiety is encompassed by an independent construct, namely neuroticism, in the Five-Factor Model of human personality.…”
Section: Discussionmentioning
confidence: 99%
“…In the Great Tit, birds from wild populations can be placed along an axis ranging from slow to fast explorers in a novel environment (Verbeek et al 1994, Drent et al 2003. This is correlated with differences in their reaction to novel objects (Verbeek et al 1994), aggressiveness (Verbeek et al 1996), recovery time and behaviour after lost contests (Verbeek et al 1999), foraging behaviour (Drent & Marchetti 1999, Marchetti & Drent 2000 and reactions to stress (Carere & van Oers 2004, Fucikova et al 2009). Artificial selection combined with cross fostering resulted in clear evidence for a genetic basis of these traits (heritabilities between 20 and 50%; Drent et al 2003, van Oers et al 2004b and in natural populations variation in personality was found to be under natural (Dingemanse & Réal 2005) and sexual selection (van Oers et al 2008).…”
Section: Smelling Out Predators Is Innate In Birdsmentioning
confidence: 99%
“…We recorded three behaviors known to reflect coping style and stress responsiveness and/or fighting propensity during handling (Carere and van Oers, 2004;Fucikova et al, 2009;Laiolo et al, 2009;Markó et al, 2013;Torné-Noguera et al, 2014). Breath rate, distress call rate, and pecking rate were recorded in the same consecutive order.…”
Section: Behavioral Testsmentioning
confidence: 99%
“…Breath rate was recorded by counting the number of breast respiratory movements within 30 s, while holding the wings fixed and also ensuring reduced disturbance by visual and sound cues (Markó et al, 2013;Torné-Noguera et al, 2014). Pecking rate and distress calling rate were subsequently quantified by counting the number of pecks and distress calls that were emitted during the next 15 s of handling (Fucikova et al, 2009;Laiolo et al, 2009). Pecking rate refers to the number of pecks against a straight finger positioned at 1-2 cm from the beak of the focal bird while holding its legs (Markó et al, 2013).…”
Section: Behavioral Testsmentioning
confidence: 99%